Working Time of the Municipal Cities’ Officials in the Grand Duchy of Lithuania in the 16th–18th centuries: The Case of Merkinė - Tubelevičiūtė, Gabija (Vilnius University Open Series, 2024)
The history of the cities of the Grand Duchy of Lithuania has in recent years attracted more and more interest in the context of Magdeburg law, city institutions, ruling elites, etc. However, to this day there has been no significant research on the working time of city officials, and certain aspects, such as the organization of work during festivals, are used as details to supplement the historical narrative. This article focuses on the working time of the municipal cities of the Grand Duchy of Lithuania in the 16th–18th centuries, using the city of Merkinė as a reference point. The study aims to find out how the working time of municipal cities was defined by normative documents, when elections and appointments of officials took place in Merkinė, how long the term of office lasted, and when the council and the court of advocatus – lay judges worked. The main part of the article is devoted to the definition of the working time (annual, monthly, weekly) of the municipal bodies of Merkinė (the council and the court of advocatus – lay judges). The work is illustrated by tables based on the data from the act books of the court of advocatus – lay judges and the council.
Keywords: GDL (Grand Duchy of Lithuania); municipal cities; Merkinė; officials; working time